Promoting Successful Projects in a Software Engineering Capstone Course - Bastarrica, María Cecilia; Salazar, Cristian (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2026: Anais do XXIX Congresso Ibero-Americano em Engenharia de Software, 2026)
Software capstone projects are successful when students achieve meaningful learning outcomes and clients obtain valuable results. For more than a decade, we have delivered a capstone course involving diverse external clients and domains, producing mostly successful projects; however, some initiatives have still fallen short. This study seeks to identify factors that foster or hinder project success in order to support instructors in structuring course dynamics and selecting appropriate projects and clients. We analyzed 18 software projects from the Spring 2024 term. At course completion, surveys were administered to both clients and student teams to evaluate technical competence, domain knowledge, time commitment, and collaborative attitude of each other. Five months later, follow-up semi-structured interviews with clients explored product value and retrospective perceptions. Survey and interview data were then cross-analyzed. Most projects were rated as successful across survey dimensions, with both groups highlighting commitment as a central factor. In less successful cases, students pointed to low client involvement or limited domain knowledge as key obstacles. At interview time, nearly all products were in use, although most required additional refinement. Even clients from less favorably rated projects generally expressed willingness to participate again, emphasizing students’ technical quality and hiring potential. Maximizing capstone success requires selecting clients who propose well-scoped, engaging projects and who understand the need for adaptive collaboration. Providing students with access to domain experts and end-users further strengthens alignment with business needs, improving both learning outcomes and practical value for clients.